Psychometric properties of the Irish Management Standards Indicator Tool - Boyd, S; Kerr, R; Murray, P (Occupational medicine (Oxford), 2016)
Work Positive is Ireland's national policy initiative to control work-related stress. Since the introduction of the UK Health and Safety Executive's Management Standards (MS) in 2004, a number of studies have been undertaken to assess the potential adaptation of the MS framework within Ireland. To investigate the dimensionality, reliability and validity of the Irish version of the MS Indicator Tool (ROI-MSIT). Between February 2011 and June 2014, we collected data from a wide range of public and private sector organizations that used the ROI-MSIT. In addition to the ROI-MSIT, respondents completed the WHO-Five Well-being Index (WHO-5). Exploratory factor analysis (EFA) was used to determine whether the ROI-MSIT maintained the structure of the UK instrument. The internal consistency of the ROI-MSIT was also assessed to determine its reliability, while its criterion-related validity was explored through correlation analysis with the WHO-5. Data were collected from 7377 participants. The factor structure of the ROI-MSIT consisted of six factors; the Demands, Control, Peer Support, Relationships and Role factors were equivalent to the original UK factors. Like the Italian version, a principal factor emerged that combined the Manager Support and Change domains. Cronbach's alpha scores ranged from 0.75 to 0.91. Finally, the ROI-MSIT's subscales and WHO-5 were positively correlated (r = 0.42-0.59, P < 0.001). The ROI-MSIT is reliable and valid, with a factor structure similar to the original UK instrument and the Italian MSIT. Further psychometric evaluation of the ROI-MSIT is recommended.